THE FACTOR STRUCTURE OF THE AXIOPSYCHOLOGICAL DESIGN OF A PERSON’S LIFE ACHIEVEMENTS AT THE EARLY ADULTS - Hulias, Inesa (PSYCHOLOGICAL JOURNAL, 2019)
The article specifies the study on axiopsychological design of personal achievements at early adulthood. The approaches to the classification of human developmental age periods at this age are discussed. The emphasis is placed on the main psychological features of early adulthood. The article outlines the range of the problems studied within the framework of the presented topic, in particular: the issues of a purpose as a meaningful determinant of the present, self-designing as a determinant of career success, choosing of a life path, understanding of private life meaning and goals, peculiarities of valuable components of life strategies of university students, living away their family and\, designing their life paths. The methodological basis for the empirical study is the principles of subjectivity, value orientations, and systemic determination. The article states that subjectivity means an individual’s position as a creator of one's own life path; subjectivity initiates all human activities and contributes to their effectiveness. The author understands subjectivity as a self-sustaining cause of being, a universal principle of the transition of an agent’s possible states into the reality of intentional objects; an individual’s system of value orientations constitutes the meaningful aspect of life perspective, and the formed hierarchy of values ​​determines the priority of certain activity spheres, vectors of life path, as well as the line of behavior; systemic determination allows an individual to objectify his/her psychological formations that set specific directions of his/her self-realization and are a form of self-realization. Particular attention is paid to the empirical research, which results are generalized and interpreted to create the factor structure of axiopsychological design of an individual’s life achievements that include nine components: disposition of self-efficacy, unwillingness to be improved, attribution, complexities of improvement, use of unproductive copings, disposition of self-regulation, traits of female gender, focus on realization, psycho-age assessment. The value factor structure of this age respondents is dominated by the first two, which we consider as the key factors.